Shakespeare the illusionist : magic, dreams, and the supernatural on film - Forsyth, Neil, 1944- (Ohio University Press, 2019)
In Shakespeare the Illusionist, Neil Forsyth reviews the history of Shakespeare's plays on film, assessing what filmmakers and TV directors have made of the spells, haunts, and apparitions-- Puck and the fairies, ghosts and witches, or Prospero's island--in his plays. A bold step forward in Shakespeare and film studies.